Acupuncture Care For Gastritis Sufferers At Griya Bimaristan Qisthi Banda Aceh - Rinaldi Habeib; Ikhwan Abdullah; Chantika Mahadini; Mayang Wulandari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Gastritis is a common digestive disorder in adults with irregular lifestyles and eating patterns. This qualitative case study collected data through four traditional examination methods: observation (Wang), hearing and smell (Wen), interviews (Wen), and palpation (Qie), complemented by documentation. The participant, a 31-year-old male with heartburn, received six sessions of acupuncture therapy. Based on the examination results, a diagnosis of Deficient Spleen and Cold Stomach Syndrome was made. The evaluation showed positive progress, with a significant reduction in heartburn, accompanied by an improvement in appetite, and the elimination of bloating and nausea. This case study is expected to provide additional material to enrich the knowledge of acupuncture students. For future researchers, this report can serve as a reference for treating stomach pain with an acupuncture approach. For the wider community, these findings reinforce acupuncture as an effective and safe therapeutic modality for functional stomach disorders, in addition to available conventional treatment options.